The genus Myxopyrum L. (oleaceae) - Kiew, Ruth (Nationaal Herbarium Nederland, 1984)
The morphology and leaf anatomy of Myxopyrum is described and a key to the species is given. Of the 15 species previously described four species and two subspecies are recognised: M nervosum BI. (synonyms M horsfieldii, M zippelii) with one subspecies coriaceum (BI.) Kiew (synonym M ellipticum), M ovatum Hill (synonyms M macrolobum, M cordatum, M philippinensis), M pierrei Gagnep. (synonym M hainanense) and M smilacifolium BI. (synonym M serrulatumy with one subspecies confertum (Kerr) Kiew. Myxopyrum enerve Steen. is Chionanthus enerve (Steen.) Kiew. Descriptions for the extra-Malesian species, M smilacifolium, is given.